Virtual banking : a guide to innovation and partnering - Schatt, Dan (Wiley, 2014)
"Technology is permanently transforming the banking industry, and digital payments are the keyElectronic Payments, Mobile Commerce, and Virtual Banking: A Guide to Innovation, Partnering, and Regulation takes a hands-on approach to competing in the modern banking environment. Former PayPal Head of Financial Innovation Dan Schatt explores the reasons behind the massive consumer migration away from traditional banks, and provides clear, actionable guidance on beating new banking models at their own game. Digital payment is the hottest topic in banking today, and is set to define the future of the industry. Consumers are rapidly abandoning traditional banks in favor of institutions that are lower-cost and more consumer-centric. Between the pace of financial regulatory reform and the cloud computing revolution, the old banking model is on the fast track to extinction. Electronic Payments, Mobile Commerce, and Virtual Banking provides the information banks need to compete in this new environment, and details the integral implementation actions that will allow them to thrive. The book discusses real-world innovations from banks, non-banks, and up and comers, and the heavy competition from the new outsource bank model. Topics include: The changing POS landscape and the need for digital wallet partnerships Shifting gears to greenfield market opportunities versus non-profitable markets Digital channel best practices for superior customer experience When to outsource, and what capabilities to truly own Case studies including PayPal, Google, Square, Facebook, Twitter, and more illustrate acceleration of innovation through banking partnerships, as well as the mechanics behind banking's biggest, scariest threats. The trick to surviving the paradigm shift is to embody innovation while providing a superior customer proposition. Electronic Payments, Mobile Commerce, and Virtual Banking: A Guide to Innovation, Partnering, and Regulation provides the inside track on managing the shift and dominating the new marketplace"--